English and Lampungnese Relational Processes - Afrianto Afrianto (Jurnal Bahasa dan Sastra, 2019)
Abstract: This research is aimed at configuring the English and Lampungnese relational pro- cess and comparing one another. This qualitative research gathered the data from English and Lampungnese lesson books. This research reveals that English and Lampungnese relational clauses demonstrates a similar configuration. Both have relational process and participants in the forms of carrier-attribute and token-value. The English relational process is indicated with copular verbs (become, sound), possessive verbs (have, contain, and consist), auxiliary verb (is, are), and modal (will and should). Furthermore, it is found that the Lampung relational process is also realized by the copular verb ( jadi/dijadiko, iyulah, yakdo, and ngeghupako). Other than a copular word, it is also realized by other relational processes, such as possessive verb (ngedok, tekughuk), modal (dapok), and other forms (sebanding, gegoh, artini, and bumakna). Further, different from English, Lampung relational clause has a unique characteristic. It is found that sometimes the clause just has participants and no process. This phenomenon will not be found in English.Keywords: clause, carrier-attribute, Lampungnese, relational process, token-valueAbstrak: Penelitian ini diarahkan untuk menelisik konfigurasi proses relasional Bahasa Inggris dan Lampung kemudian membandingkannya satu sama lain. Data penelitian ini dikumpulkan dari buku pelajaran bahasa Inggris dan Lampung. Penelitian ini mengungkapkan bahwa klausa relasional bahasa Inggris dan Lampung memiliki konfigurasi yang serupa. Keduanya memiliki proses relasional dan partisipan dalam bentuk carrier-attribute dan token-value. Proses rela- sional dalam bahasa Inggris diindikasikan oleh kata kerja kopula (become, sound), kata kerja kepemilikan (have, contain, dan consist), kata kerja bantu (is, are), dan modal (will dan should). Lebih jauh, ditemukan juga bahwa proses relasional dalam bahasa Lampung direalisasikan oleh kata kerja kopula ( jadi/dijadiko, iyulah, yakdo, dan ngeghupako). Selain itu, proses rela- sional juga ditunjukkan oleh penggunaan kata kerja kepemilikan (ngedok dan tekughuk), modal (dapok), dan bentuk lain (sebanding, gegoh, artini, dan bumakna). Kemudian, berbeda dengan bahasa Inggris, klausa relasional dalam bahasa Lampung memiliki karateristik yang unik ka- rena ditemukan bahwa terkadang klausa relasional hanya memiliki partisipan tanpa ada proses. Fenomena ini tidak akan ditemukan dalam bahasa Inggris.Kata-kata kunci: klausa, carrier-attribute, Bahasa Lampung, proses relasional, token-value